Peranan Sentral Guru Agama Hindu dalam Pencapaian Tujuan Pendidikan Nasional di Indonesia dan Pembangunan Karakter Bangsa yang Berakhlak Mulia, Jujur, Terampil, Berhati Suci dan Bersih Lahir Batin - Ni Nengah Selasih (UHN IGB Sugriwa Denpasar, 2015)
The teachers of Hindu religion classes play central role in the effort to reach the goalof the national education as well as to build the characters that include honesty, skillfullness,clean and good-heartedness, as described in the national standard of education regulationNo 20/2003 in which it states that the curriculum has to provide religious education (Pasal37 UU Sisdiknas). The government attention to the education is implemented too by theissue of the Regulation on Teachers and Lecturers which states that teachers are professionaleducators with main duty to educate, teach, guide, train, and evaluate the students in theformal elementary, secondary, and high schools (UU RI No. 14/2005) Purwanto(2004:10).Education is the intentional enlightening from the adult to the younger ones inrelation to their development in order to make them useful for themselves and in the society”The Indonesian national education systemas stated in UU No.2/1989 Bab, II, pasal 4,states that the goal of the education is to develop a complete Indonesia people who arereligious, good in their characters, have good knowledge and skills, healthy physicallyand mentally, independent, responsible for the society and nation. In line with that, theHindu teachers should refer to the Vedic teachings and consider the physical, psychological,and social environments of study, the life as students (Sisya/Brahmacari), their roles (Acarya),the curriculum, the mteaching methods, as well as the goal of the education. These allshould be centered on• teaching with the emphasis on directing and motivating to reach the character building• facilitating that through learning experience• helping to develop attitudes, values, and self adaptationAt schools teachers should commit themselves to be 1) role models, 2) inspirators, 3)motivators, 4) regulator, 5) evaluator besides having good vision. Without these all, thegoal of education will fail.